2020
DOI: 10.1109/access.2020.2992653
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Low-Profile Luneburg Lens Based on a Glide-Symmetric Metasurface

Abstract: This paper presents a two-dimensional low-profile Luneburg lens that is designed by using a glide-symmetric metasurface. The entire lens consists of two mirrored metal plates with periodic metal pins, and the pins on one plate are glided exactly a half period of the unit cell compared with the pins on the other plate. The proposed design has not only a stable refractive index over a wide operating band but also no dielectric loss compared to other metamaterial-based lenses. In addition, it is easy to manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…These curves are more circular in the case of glide symmetry, especially as the frequency increases. This phenomenon was first reported in [13] and was later used for the design of planar lenses [60]- [62]. More details about these designs are provided in Section V.…”
Section: A Dispersionmentioning
confidence: 69%
See 1 more Smart Citation
“…These curves are more circular in the case of glide symmetry, especially as the frequency increases. This phenomenon was first reported in [13] and was later used for the design of planar lenses [60]- [62]. More details about these designs are provided in Section V.…”
Section: A Dispersionmentioning
confidence: 69%
“…The benefits of glide symmetries are not limited to holey structures. For example, glide-symmetric metallic pins also present advantages with respect to conventional pins, as demonstrated in [61], [62], [88]. Similar benefits were demonstrated in planar technologies [89]- [91].…”
Section: E Lensesmentioning
confidence: 71%
“…Additionally, it has been demonstrated that glide-symmetric structures are less dispersive [12,13] and can provide a higher effective refractive index [13][14][15][16], effective permeability [17], and level of anisotropy [18], compared to their non-glide counterparts. These properties have been used to design planar lenses in [13,[19][20][21][22]. Furthermore, while the stop-band between the first two modes is suppressed in glide-symmetric structures, a large stop-band exists at higher frequency [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the designed lens exhibits strong anisotropy, which degrades the scanning performance of the lens. Alternatively, two-dimensional (2D)-graded index lenses can be realized using concentric dielectric cylinders [16,17] or mimicked with quasi-periodic structures [18][19][20][21][22][23] or geodesic surfaces [5,[24][25][26]. However, the scanning is reduced to one dimension in the 2D lenses.…”
Section: Introductionmentioning
confidence: 99%